CRISPR/Cas9 Mutagenesis by Translocation of Cas9 Protein Into Plant Cells via the Agrobacterium Type IV Secretion System - Schmitz, Daan J.; Ali, Zahir; Wang, Chenglong; Aljedaani, Fatimah; Hooykaas, Paul J. J.; Mahfouz, Magdy; de Pater, Sylvia (Frontiers in Genome Editing, 2020)
Clustered regularly interspaced short palindromic repeats (CRISPR)/CRISPR-associated protein 9 (Cas9) is a powerful tool for genome engineering in plants. The RNA-guided Cas9 endonuclease is usually delivered into plant cells as a DNA construct encoding Cas9 and the single guide RNA (sgRNA). However, constitutive expression of nucleases may cause off target mutations. In addition, DNA constructs can integrate into the host genome, causing mutations and complicating regulatory approval. Instead of DNA, here we deliver Cas9 through the Agrobacterium T4SS, accomplished by fusion of the VirF T4SS translocation peptide to Cas9 (NCas9F). Co-cultivation of Agrobacteria expressing NCas9F with yeast (Saccharomyces cerevisiae) harboring a sgRNA targeting CAN1 showed that NCas9F was translocated via T4SS and induced targeted mutations in the yeast genome. Infiltration of Nicotiana benthamiana leaves with Agrobacteria expressing NCas9F and sgRNA-PHYTOENE DESATURASE (PDS) resulted in targeted modifications at the PDS locus, albeit at a very low rate. In order to increase the mutation frequency NCas9F protein was co-transported with a T-DNA encoding sgRNA-PDS. Next generation sequencing confirmed that this resulted in targeted mutations at the PDS locus with a similar distribution but at a 4 fold lower frequency as the mutations obtained with a T-DNA encoding both Cas9 and sgRNA-PDS. Similarly, infection with Tobacco rattle virus (TRV) encoding sgRNA-PDS2 combined with NCas9F protein translocation resulted in an equally high frequency of PDS mutations in N. benthamiana compared to T-DNA encoded sgRNA-PSD1 combined with NCas9F protein translocation. Our results revealed that translocation of NCas9F protein via the Agrobacterium T4SS can be used for targeted mutagenesis in host cells instead of the permanent and constitutive expression of Cas9 from a T-DNA.